Exploring the Effect of Chicano Studies Courses on Student Success at CSU Channel Islands - Brunk, Avery; Lovekin, Katherine; Martos, Andrew; Soderlund, Christina (The PUMP Journal of Undergraduate Research, 2021)
California State University, Channel Islands (CSUCI) has long embraced the ideal of access to education while seeking to provide high quality degrees for its students. The success of obtaining Hispanic-Serving Institutions grants has been helpful in providing resources for programs offering educational interventions for both Hispanic students and for those from other backgrounds. We have seen anecdotal evidence that Hispanic students who enroll in Chicano Studies courses tend to find community and consequently success. In this project, we use the enormous storehouse of CSUCI data to explore the effectiveness of specific Chicano Studies courses on student success. We apply regression analysis, hypothesis tests for proportions, t-tests, and tests of independence to investigate the quantitative evidence for what we have seen anecdotally.